2012
DOI: 10.3897/zookeys.242.3974
|View full text |Cite
|
Sign up to set email alerts
|

Neoethilla, a new genus for the first record of the Ethillini from the New World (Diptera, Tachinidae, Exoristinae)

Abstract: New genus Neoethilla gen. n., is described to include two New World nominal species formerly recognized as valid species in Winthemia Robineau-Desvoidy: Exorista ignobilis van der Wulp and Winthemia antennalis Coquillett. Winthemia antennalis is proposed as a junior synonym of Exorista ignobilis syn. n. Neoethilla ignobilis comb. n. is removed from the Winthemiini and placed in the tribe Ethillini (Exoristinae) based on a study of the external features of adults, male terminalia, female reproductive system, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…These features indicate that the composition of the Ethillini has been weakly founded, and its monophyly was questioned by Tschorsnig (). Cerretti et al () argued that three monophyletic groups can be identified within Ethillini, and these groups are recognized as monophyletic in the current analysis: a Phorocerosoma group (here represented only by Phorocerosoma ); an Ethilla group (clade BG), characterized by the laying of unembryonated eggs (7:0); and a Paratryphera group (clade BI), which lays embryonated eggs (7:1). The laying of unembryonated eggs provides homoplasious autapomorphic support to clade BC, wherein the Exoristini are positioned as sister group of ( Medina + ((Winthemiini + Phorocerosoma ) + Ethilla group)).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…These features indicate that the composition of the Ethillini has been weakly founded, and its monophyly was questioned by Tschorsnig (). Cerretti et al () argued that three monophyletic groups can be identified within Ethillini, and these groups are recognized as monophyletic in the current analysis: a Phorocerosoma group (here represented only by Phorocerosoma ); an Ethilla group (clade BG), characterized by the laying of unembryonated eggs (7:0); and a Paratryphera group (clade BI), which lays embryonated eggs (7:1). The laying of unembryonated eggs provides homoplasious autapomorphic support to clade BC, wherein the Exoristini are positioned as sister group of ( Medina + ((Winthemiini + Phorocerosoma ) + Ethilla group)).…”
Section: Discussionmentioning
confidence: 77%
“…Another issue emerging from this analysis is the probable polyphyly of the Ethillini as currently defined (Cerretti et al , ). Ethillini are traditionally defined as sharing three character states: strongly convex lower calypter, katepimeron setulose, and ovipositor short and unmodified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exorista ignobilis was assigned to Winthemia Robineau-Desvoidy byReinhard (1931: 16) and stayed in this genus until recently recognised as the sole New World member of the Ethillini and placed in the new genus Neoethilla byCerretti et al (2012). Its distribution is thought to be limited to United States and Mexico(Cerretti et al 2012) and reports of the species from South America in the following works are likely based on misidentifications of…”
mentioning
confidence: 99%
“…Note: one or more Winthemia species:Reinhard (1931: 17, Argentina, Chile),Aldrich (1934: 44, Argentina, Chile),Cortés (1946: 175, Chile),Cortés (1948: 124, Chile),Cortés and Hichins (1969: 63, Chile),Henry (1987: 200, Chile),Coelho et al (1989: 275, as "ignobillis", Argentina, Bolivia, Brazil, Chile, Colombia, Equador, Peru, Venezuela), Vergara de Sánchez and Raven (1990: 100, Chile) andGonzález (1992b: 180, 183, Chile) Cerretti et al (2012). suspected that the species called W. ignobilis in Chile and Argentina might be Winthemia reliquaCortés & Campos, 1971, which Coelho et al (1989 has treated as a synonym of Winthemia trinitatisThompson, 1963.…”
mentioning
confidence: 99%